An Analysis of Similes in Taylor Swift’s Selected Songs: Pedagogical Implications for English Literature Teaching - Indawan Syahri; Asti Gumartifa; Della Liyundzira (Universitas Islam Negeri Palopo, 2026)
This study analyzes the types and meanings of similes in sixteen selected Taylor Swift songs and explains their pedagogical implications for English literature teaching. It addresses the need to connect stylistic analysis of popular song lyrics with figurative-language instruction, literary interpretation, vocabulary development, and critical reading in English education. The study employed a qualitative descriptive design using stylistic, document-analysis, and text-oriented procedures. Thirty-eight simile units were identified through repeated reading and recorded in a coding sheet. The units were classified as open or closed similes, interpreted contextually, and organized into semantic categories through qualitative content and thematic analysis. The analysis identified thirty-eight similes. Closed similes dominated with thirty-three occurrences, whereas open similes occurred five times. Eleven semantic categories emerged: love, admiration, disappointment, surprise, memory, confusion, satisfaction, frustration, sincerity, social positioning, and enjoyment. The comparisons construct emotional imagery, narrative intimacy, evaluation, identity, and reflective meaning. The findings can support English literature, stylistics, figurative-language, reading, and vocabulary courses. Teachers may use selected lyrics as authentic literary materials for identifying comparative markers, distinguishing simile types, inferring shared features, interpreting emotional effects, discussing themes, and producing original figurative expressions through structured classroom activities. This study advances previous song-lyric research by integrating structural classification, semantic interpretation, and pedagogical application in one analytical framework. Rather than merely listing figurative-language types, it demonstrates how similes function as meaning-making devices and translates the findings into a scaffolded approach for teaching literary interpretation through culturally familiar popular texts.